ANCESTORCENTRISM AND THE GBEWAAH DEVELOPMENT PARADIGM; A TRANS-LEVEL PARAXIS - Dr. Abu Tia Jambedu (Sciental Journals Publishing, 2025)
This paper advances Trans-Development as a novel ontological and cosmological framework emerging from Ancestorcentrism and operationalised through the Gbewaa Development Paradigm. In response to the limitations of GDP-centred, technocratic, and sectoral development models, the study introduces the Trans-Level as a meta-integrative space where development is governed by communal ethics (axiology), validated through lived experience and ancestral authority (gnosiology), and enacted through relational governance. Drawing on African Indigenous Knowledge Systems and the lived cosmologies of the Mole–Dagbamba peoples of Ghana, Togo, and Burkina Faso, the paper repositions ancestral wisdom as a living epistemic and moral foundation for science, leadership, and development.The core finding reveals that Trans-Level development moves beyond science, data, and quantitative indicators by capturing lived realities—peace, social harmony, ecological balance, and intergenerational continuity—that conventional development indices cannot adequately measure. Development is thus redefined as a cyclical process that transforms wealth (total potential) into worth (realised communal wellbeing), culminating in Gross Societal Wellbeing (GSW) rather than economic growth alone.The study concludes that sustainable development cannot be meaningfully achieved through indicators alone. It recommends that development policy and practice adopt holistic wellbeing frameworks, including context-specific Gross National Wellbeing (GNW) metrics grounded in Indigenous cosmologies and communal values, to assess whether development interventions genuinely translate into happiness, peace, and national harmony at community and national levels.
Keywords: Ancestorcentrism; Trans-Development; Gbewaa Development Paradigm; Indigenous Knowledge Systems; Gross Societal Wellbeing; System Transdisciplinarity.